"The Apple Way": Foucault, Design, Consumerism, and the Shaping of Apple Subjects. (2nd January 2023) - Gaughwin, Melinda
Abstract: The contribution Michel Foucault's thoughts on power, in particular his ideas of subjectivity, freedom, and action, might have to the study of design's ontological shaping of people is an emerging field of inquiry in the academy. Using a Foucauldian lens, this paper presents findings from semi-structured interviews with iPhone® users that speak to the ways Apple consumers are constituted into Apple subjects by what I refer to as "the Apple Way." The ineradicable relationship between discourses of design and consumerism and their imperative to "better" human life is presented as a starting point. The iPhone as a technological device that "makes life better" for Apple consumers is critiqued; data reveals an uneasy reliance people have on the iPhone for their everyday life.